Cloning and Characterization of a Retroviral Plasmid, pCC1, for Combination Suicide Gene Therapy. (March 2000) - Kuiper, Marcel; Sanches, Raquel; Gäken, Joop A.; Bignon, Yves-Jean
Introduction of the herpes simplex virus thymidine kinase ( HSV-TK ) gene into mammalian cells confers specific sensitivity to killing by the anti-herpes drug ganciclovir (GCV). This gene has therefore been used in a number of cancer gene therapy protocols as a therapeutic gene. However, the therapeutic efficacy of HSV-TK /GCV in cancer gene therapy experiments can be augmented by additional therapeutic genes. We have cloned a retroviral plasmid, pCC1, containing a fusion gene of HSV-TK and Sh-ble driven by an internal simian virus 40 early promoter. This gene encodes a fusion protein that confers GCV sensitivity and Zeocin™ resistance when introduced into mammalian cells. A multiple cloning site (MCS) allows the introduction of a second therapeutic gene under the transcriptional control of the Moloney murine leukemia virus 5′ long terminal repeat. We have generated packaging cell lines electroporated with pCC1 or pCC1 rtIL-2 S (rat interleukin-2 gene cloned in the sense direction in the MCS), the supernatants of which transfer GCV sensitivity only, or both GCV sensitivity and rtIL-2 production, respectively to rat ovarian cancer cells. This plasmid may be useful for the study of combination suicide gene therapy strategies.